Identification of azabenzimidazoles as potent JAK1 selective inhibitors. Issue 1 (1st January 2016) - Vasbinder, Melissa M.; Alimzhanov, Marat; Augustin, Martin; Bebernitz, Geraldine; Bell, Kirsten; Chuaqui, Claudio; Deegan, Tracy; Ferguson, Andrew D.; Goodwin, Kelly; Huszar, Dennis; Kawatkar, Aarti; Kawatkar, Sameer; et al.
Graphical abstract: Abstract: We have identified a class of azabenzimidazoles as potent and selective JAK1 inhibitors. Investigations into the SAR are presented along with the structural features required to achieve selectivity for JAK1 versus other JAK family members. An example from the series demonstrated highly selective inhibition of JAK1 versus JAK2 and JAK3, along with inhibition of pSTAT3 in vivo, enabling it to serve as a JAK1 selective tool compound to further probe the biology of JAK1 selective inhibitors.